Readings of otherness in Colombian legal multiculturalism (2018)
The purpose of this paper is to show that the multiculturalism of legal reception in Colombia implies a restricted form of otherness that comes from ethnic identity. This otherness sets a livable life paradigm and, at the same time, builds the idea of isolation (field) from the non-essential other. The main hypothesis is that in the constituent debates of the nineties, otherness appears as a concept presupposed by multiculturalism that simplifies the forms of appearance of the other and with it sets a paradigm of life that matters, that is, a specific type of biopolitics. In order to develop this hypothesis, first the document will show that multiculturalism in Colombia has mainly had a legal reception, which delimits a specific type of otherness (ethnic identity). Second, it explains the legal configuration of the other's paradigm from ethnic identity. Finally, it proposes a critique of this paradigm, from an enlarged concept of culture, as well as from the perspective of field and livable life, using theoretical resources in the works of Stuart Hall and Roberto Esposito. © 2018 Universidad del Norte. All rights reserved.